PJMHS 2022
DOI: 10.53350/pjmhs221651018
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of HCV in Children with Thalassemia Major

Abstract: Objective: The purpose of this study is to determine the prevalence of HCV in children presented with thalassemia major. Study Design: Retrospective/Cross-sectional study Place and Duration: Islamic international medical college Riphah university, From March, 2021 to August, 2021 Methods: There were 72 children with ages 3-15 years were presented in this study. Age, gender, and weight were tallied after informed written permission was obtained from each participant. Both the enzyme-linked immunosorbent assay (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…32 In addition, a study in Pakistan reported that 26 out of 72 thalassemic children aged between 3 and 15 years were HCV positive, and concluded that blood transfusion, ear piercing, and dental procedures were the major reasons for acquiring HCV infection. 33 In conclusion, our study findings showed that there was a very low incidence of HCV with no A, B, or E viral hepatitis in three hospitals serving children in Cairo Egypt. However, additional research studies with larger study sample sizes from more hospitals in various parts of Egypt are necessary.…”
Section: Hcv Infection and Patient's Medical Historymentioning
confidence: 50%
“…32 In addition, a study in Pakistan reported that 26 out of 72 thalassemic children aged between 3 and 15 years were HCV positive, and concluded that blood transfusion, ear piercing, and dental procedures were the major reasons for acquiring HCV infection. 33 In conclusion, our study findings showed that there was a very low incidence of HCV with no A, B, or E viral hepatitis in three hospitals serving children in Cairo Egypt. However, additional research studies with larger study sample sizes from more hospitals in various parts of Egypt are necessary.…”
Section: Hcv Infection and Patient's Medical Historymentioning
confidence: 50%